The Impact of Macroprudential Supervision Tools on Financial Soundness in the Southern Mediterranean Countries - Ouhibi, Saoussen; Ghabri, Mayassa; Hammami, Sami (Asian Journal of Empirical Research, 2017)
This paper presents a macroprudential approach to supervision the soundness of the financial system in the southern Mediterranean countries by using a panel data. The objective of this research is to estimate the impact of the macroprudential instruments on the banking system solidity of the southern Mediterranean countries between 2000 and 2013. The empirical results suggest the importance of macropudential tool in the financial system.